2010
DOI: 10.3989/scimar.2011.75n2369
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and hystopathology of <i>Mullus barbatus</i> and <i>Citharus linguatula</i> (Pisces) from two sites in the NW Mediterranean with different degrees of pollution

Abstract: SUMMARY: The usefulness of fish parasite communities as bioindicators of environmental stress was tested on two benthic fish species, the red mullet (Mullus barbatus) and the spotted flounder (Citharus linguatula), during the spring of 2006 at two sites of the Catalan coast (northwestern Mediterranean): an anthropogenic-impacted area located close to the city of Barcelona, and a less polluted area close to Blanes (Girona). Gonadosomatic and hepatosomatic indices and condition factor were determined for the fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Their aetiology still remains unknown, and they have not been associated so far with any specific parasitic organism (MacKenzie, 1979;Munday and Brand, 1992;Nowak, 1996;Nowak et al, 2004;present work). Carreras-Aubets et al (2010) also reported the presence of these structures in Mullus barbatus and Citharus linguatula sampled in the continental shelf, in an area close to this study, and proposed a link between pollution and presence of these cysts, as Munday and Brand (1992) also suggested in other fish species. High organic carbon (Liquete et al, 2010), heavy metal (Sánchez-Cabeza et al,1999;Palanques et al, 2008) and organic pollutants values (PCBs, DDT, etc.)…”
Section: Discussionmentioning
confidence: 50%
“…Their aetiology still remains unknown, and they have not been associated so far with any specific parasitic organism (MacKenzie, 1979;Munday and Brand, 1992;Nowak, 1996;Nowak et al, 2004;present work). Carreras-Aubets et al (2010) also reported the presence of these structures in Mullus barbatus and Citharus linguatula sampled in the continental shelf, in an area close to this study, and proposed a link between pollution and presence of these cysts, as Munday and Brand (1992) also suggested in other fish species. High organic carbon (Liquete et al, 2010), heavy metal (Sánchez-Cabeza et al,1999;Palanques et al, 2008) and organic pollutants values (PCBs, DDT, etc.)…”
Section: Discussionmentioning
confidence: 50%